Clinical Challenges on Adhesive Dentistry on its 60th Anniversary - Sartori MS, PhD, Neimar (Odovtos - International Journal of Dental Sciences, 2015)
Adhesive dentistry allowed restoring lost tooth structures using Minimally Invasive direct or indirect bonded restorations. Adhesive systems and bonding techniques have been constantly evolving since the introduction of Sevriton Cavity Seal, in 1940 by Oskar Hagger. As we celebrate the 60th anniversary of adhesive dentistry in 2015 the future of the Minimally Invasive Adhesive Dentistry is more promising than ever. A better understanding of long-term resin-dentin bonds interaction is guiding the development of materials and techniques that overcome the limitation of current bonding agents and restorative procedures. A brief statement would be stated.